.: . - Thaha, Salmiyah; Diputra, Indra; Permatasari, Nur Indah (Al-Buhuts, 2023)
It is feared that the unemployment rate among educated students will continue to increase if universities as degree-producing institutions cannot direct their students and alumni to the world of work after graduation. Coupled with the lack of entrepreneurial motivation among the younger generation, this is a serious concern for various parties. This research aims to foster students' interest and awareness of entrepreneurship through making business plans, increasing motivation to learn entrepreneurship, and introducing students to the preparation of business plans in developing character as entrepreneurs. Equipping students to start a business by designing a canvas business model. The sample used in this study was 68 respondents. Data collection techniques with observation, questionnaires, or interviews, the sampling technique uses purposive sampling. as an evaluation tool during the business run.Keywords: Entrepreneurial interest, Business Plan, Business Model Canvas. The results showed that there is a significant relationship between interest in entrepreneurship with the creation of a business plan and business model canvas on students with a regression value Y = 1.757 + 0.431 X1 + 0.179 X2, the significance value of the significance of the research results 0.00000 <0.05, then the relationship of the three variables is significant. The correlation coefficient value r of 0.647 is a strong and positive relationship between entrepreneurial interest and making business plans and business model canvases. A good business plan uses language that is easy to understand, short, concise, and clear. The business model canvas can facilitate future business design and as an evaluation tool while the business is running.